Effects of indolebutyric acid concentration and time of incubation on rooting and growth of Pyrus calleryana L. Shoots obtained in vitro - Pasqual, Moacir; Lopes, Patrícia Andrade (Pesquisa Agropecuaria Brasileira, 1991)
The purpose of the present work was to determine a incubation time in a concentration of indolebutyric acid to make possible good rooting and growth of Pyrus calleryana shoots obtained in vitro. Indolebutyric acid was used at 10, 20 and 30 mg/l in incubation by 6, 12, 24 and 48 hours. After incubation, 50% of explants were transferred to "MS" medium (1/2 strength) under in vitro conditions and evaluated at 15 days of incubation by means of rooting percentage and plant growth; the other half was removed to substract (soil and vermiculit) and kept in green house (acclimation conditions). The evaluation was made at 15 and 45 days by the plant development and number of leaves. The explants rooted in vitro showed smaller growth. Higher number of leaves was obtained with IBA 30 mg/liter by 24 and 36 hours, and higher strength of root with IBA 30 mg/liter by 25,3 hours. After 45 days, vigorous plants were obtained in 30 and 50 mg/liter of IBA by 25 and 20 hours, respectively.